Obstacles to the development of Food Waste Law in England - Youyuenyong, Pedithep (Journal of Public Administration Chiang Rai Rajabhat University, 2021)
This article aims to discuss the development of food waste policy and the prevailing trends in food waste law in England that took place between 2015 and 2019. The discussion also includes the concept of enacting the implementing legislation of the EU Waste Framework Directive, the recommendations of mandatory food waste reduction, the reports and recommendations on the issues of food waste addressed in recent years, and reinforcement measures rectified by granting the power (or legal entities) for all agencies involved in food waste management. The discussions are summarized in terms of how concept of the mandatory food waste reduction in England can be put into effect before a further discussion of food waste stakeholders participating in long-term legal reform is set up, and what problems and obstacles are encountered in food waste law reform. In addition, the discussions are analysed in terms of how these obstacles can be removed or how development of the food waste law in England can be fostered.